ASPECTS OF ENSURING THE QUALITY OF COMPUTER SCIENCE EDUCATION - Ilyasova, Zukhra K. (International Journal of Psychosocial Rehabilitation, 2020)
The didactic functions of the informatics course in the formation of the content elements of knowledge necessary in the professional activity of a specialist adapted to modern conditions are revealed. The general methodology, systems and tools, methods, methodical methods of realizing the task were developed and tested on the course material of informatics